Matrix Analysis of ECG Parameters May be a Way to Improve Quality of Functional State Monitoring during Exercising - Jonas Poderys; Liepa Bikulčienė; Eugenijus Trinkūnas; Kristina Poderienė; Alfonsas Buliuolis; Alfonsas Vainoras (Lithuanian Sports University, 2018)
Research background. The aim of this study was to compare the peculiarities of dynamics of cardiovascular functional state indices during bicycle ergometry by applying the steep or slow increase in workload. Methods. Twenty five  males attending health promotion sport clubs took part in two cardiovascular testing procedures performing graded exercise stress, i.e. increasing the workload every min, and increasing the workload every 6 min. They exercised till the inability to continue the task or when distressing cardiovascular symptoms supervened. 12 Lead ECG was recovered and analysed. Results. The steep increase of registered cardiovascular parameters was observed at onset of exercising and the rate of it depended on the increase rate in workload. Registered maximal changes of heart rate, JT interval, and the ratio JT/RR as a functional state index at the moment of refusing to continue the graded exercise test were of the same level while applying the steep or slow increase in workload. Conclusions. The rate of increase in workload determines the mobilization rate but not the degree of increase of ECG parameters. Maximal changes of heart rate, JT interval, and the ratio JT/RR as functional state index at the moment of refusing to continue the graded exercise test were the same level while applying the steep or slow increase in workload. Keywords:  cardiovascular system, graded exercise stress, functional state.